From Growth to Resilience: A Critical Gaze to the Evolution of Development Discourse - Neupane, Bhuwani (Journal of Productive Discourse, 2025)
This study offers a critical examination of the transformative evolution of development discourse—from traditional, growth-centered paradigms to more recent frameworks that incorporate sustainability and resilience. Development thinking, once dominated by modernization and dependency theories, has gradually evolved through critical insights from post-development scholars and increasing awareness of global environmental and socio-economic challenges. The concept of sustainability in development emphasizes the interdependence of economic, social, and environmental systems, while resilience highlights the capacity to adapt to and recover from disruptions. In this context, the study explores how sustainability and resilience have become central to contemporary development discourse and practice. A qualitative desk review methodology has been employed, through which relevant literature is selectively and synthetically analyzed. The findings indicate that integrating the three concepts—development, sustainability, and resilience—is crucial for addressing complex development challenges linked to climate change, inequality, and political instability. The study concludes by proposing future research directions, including the operationalization of integrated frameworks in diverse contexts and the role of local knowledge systems in advancing sustainable and resilient development pathways.